Activity of Bdellovibrio on Sludge bacteria and its potential use for cleaning of Membrane Bioreactors - Özkan, Melek; Celik, Merve Akay; Karagoz, Pinar; Yilmaz, Hilal; Sengezer, Cisel (Elsevier Science Bv, 2014)
[No abstract available]